Living with Peritoneal Dialysis in Trentino (North Italy). Interdisciplinary Research Collaboration between Anthropology and Nephrology - Roberta Raffaetà; Giandomenico Nollo; Diana Zarantonello; Alessandro Laudon; Giuliano Brunori; Marta Rigoni (AM. Rivista della Società Italiana di Antropologia Medica, 2020)
Living with Peritoneal Dialysis in Trentino (north Italy). Interdisciplinary Research Collaboration between Anthropology and Nephrology We illustrate how peritoneal dialysis (PD) is perceived and managed by people suffering of chronic kidney disease as an alternative to hemodialysis (HD). PD can be performed at home; HD requires hospitalization. PD is underused even if it seems to offer a number of potential benefits, among which increased autonomy and quality of life. Our article sheds light on how PD managment—including logistic, technical, social and emotional aspects—is mostly a patient’s responsibility, while HD is carried out by health professionals at the hospital. The article, therefore, critically analyses the autonomy provided by PD and reconsiders its susteinability and costs in light of people everyday experiences of living with this technologyVivere con la dialisi peritoneale in Trentino. Una ricerca interdisciplinare tra antropologia e nefrologiaQuesto articolo illustra come la dialisi peritoneale è percepita e gestita dalle persone che soffrono di malattia renale cronica in alternativa all’emodialisi. La dialisi peritoneale può essere gestita a casa mentre l’emodialisi richiede l’ospedalizzazione. La dialisi peritoneale non è ampiamente utilizzata anche questa sembra offrire una serie di vantaggi, tra questi maggiore autonomia del paziente e migliore qualità di vita. La nostra indagine mette in luce come la gestione della dialisi peritoneale (che include aspetti logistici, tecnici, sociali ed emotivi) è principalmente responsabilità del paziente, mentre l’emodialisi è gestita dai sanitari all’ospedale. L’articolo procede quindi a un’analisi critica dell’autonomia offerta dalla dialisi peritoneale e riconsidera la sua sostenibilità e i suoi costi alla luce delle esperienze dei pazienti che vivono tutti i giorni con questa tecnologia.